Emergency remote teaching in covid-19 times: teacher education and digital technologies (Revista Internacional de Formação de Professores, 2020)
This study discusses the continuity of classes during the Covid-19 pandemic and the instrumentalization of digital technologies via a teacher training course, promoted by a private teaching network, focused on Emergency Remote Education (ERE). This qualitative research is in the area of Education and Interactive Digital Technologies. The reflections point to the relevance of teacher training in the ERE scenario. The study revealed the need to offer digital spaces for the interaction between teachers and a digital repository for the sharing of class content between teachers, which would represent a reduction in work overload.
Keywords: Emergency Remote Education.; Covid-19.; Teacher Education.; Interactive Digital Technologies.